2021
DOI: 10.3389/fphys.2021.554026
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Surgical Pleth Index and Analgesia Nociception Index in Healthy Volunteers and Parturients

Abstract: Various commercially available nociception devices have been developed to quantify intraoperative pain. The Surgical Pleth Index (SPI) and Analgesia Nociception Index (ANI) are among the analgesic indices that have been widely used for the evaluation of surgical patients. This study aimed to evaluate the clinical performance of the SPI and ANI in conscious healthy volunteers and parturients. Ten healthy volunteers and 10 parturients participated in this study. An algometer was used to induce bone pain in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Moreover, in a study performed in healthy volunteers and parturients by Choi et al [57], an algometer was used to induce bone pain in volunteers until they rated their pain as five on the NRS; this procedure was repeated during the administration of remifentanil or normal saline. Parturients' SPI data were collected for 2 min when they rated their pain levels as 0, 5, or 7 on an NRS.…”
Section: Consciousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a study performed in healthy volunteers and parturients by Choi et al [57], an algometer was used to induce bone pain in volunteers until they rated their pain as five on the NRS; this procedure was repeated during the administration of remifentanil or normal saline. Parturients' SPI data were collected for 2 min when they rated their pain levels as 0, 5, or 7 on an NRS.…”
Section: Consciousnessmentioning
confidence: 99%
“…In addition, in a study conducted in conscious patients by Choi et al [57], the SPI and ANI were compared, and at NRS 5, the SPI showed similar values irrespective of remifentanil administration, whereas the ANI showed significantly lower values on remifentanil administration. Thus, although both the SPI and ANI were effective indices for detecting pain in healthy volunteers, the SPI showed better performance in the perception of pain intensity, suggesting that the SPI may be useful for pain evaluation even in conscious patients.…”
Section: Analgesia Nociception Index (Ani)mentioning
confidence: 99%
“…Several studies have compared ANI to other nociception monitoring techniques, that is, comparing ANI to SPI [ 21 24 ] and comparing ANI to pupillometry [ 25 ]. ANI and SPI are altered by nociceptive events under both inhalation [ 23 ] and propofol anesthesia [ 24 ].…”
Section: Ani For Pain/nociception Assessmentmentioning
confidence: 99%
“…The Analgesia Nociception Index (ANI) is a new monitor utilized in human medicine to quantify the balance between nociception and antinociception [ 5 , 11 , 15 , 16 ], while in veterinary medicine, Parasympathetic Tone Activity (PTA) serves a similar purpose [ 17 , 18 , 19 ]. The PTA signal is acquired in real time using a lead II electrocardiogram (ECG) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%